Conversion of Waste Cooking Oil with Transesterification Process in Ultrasonicator using SrO-KF Catalyst - Santoso, Aman; Ramadhan, Laili; Susilo, Bambang; Sukarni, Sukarni; Wijaya, Anugrah; Sumari, Sumari; Muntholib, Muntholib; Pramesti, Indah Nur; Asrori, Muhammad Roy (Orbital: The Electronic Journal of Chemistry, 2024)
Waste cooking oil has the potential to be a raw material for biodiesel. The use of heterogeneous catalysts and ultrasonicator will optimize the transesterification and environmentally friendly. Transesterification study of waste cooking oil with SrO-KF nano catalyst has been carried out. This researchs were: refinement of waste cooking oil, synthesis of SrO-KF nano-catalyst, and the transesterification. The catalyst applied ratio of 1:1, 1:2, and 1:3 of SrO:KF with concentrations of 2%, 3% and 4% by weight of oil respectively. The results of heterogeneous catalyst using XRD and SEM showed that SrF2, SrO and KF compounds had been formed. The optimum transesterification conditions were obtained on SrO-KF catalyst (1:2), concentration of 4% (w/w) with a yield of 84.4% (w/w). The methyl ester of waste cooking oil has density of 884 kg/m3, acid number of 0.48 mg/g, and viscosity of 4.2 cSt. Methyl esters of waste cooking oil were composed of 25.14% methyl palmitate and 33.65% methyl elaidate, 11.27% methyl linoleate, 10.14% methyl lauric and a mixture of methyl esters from waste cooking oil has the potential to be used as biodiesel.